Reguladores vegetais e a anatomia da folha de tomate (Lycopersicon esculentum Mill.) cv. Ângela Gigante - Martins, Maria Bernadete Gonçalves [UNESP]; Castro, Paulo Roberto de Camargo e (Universidade de São Paulo (USP), Escola Superior de Agricultura Luiz de Queiroz (ESALQ), 1999)
O objetivo do presente trabalho foi verificar os efeitos dos reguladores vegetais GA3 50 mg.l-1, NAA 100 mg.l-1, CCC 1500 mg.l-1 e SADH 3000 mg.l-1 em folhas de tomate, Lycopersicon esculentum Mill. cv. 'Ângela Gigante'. Os promotores de crescimento aumentaram o número de estômatos por milímetro quadrado na epiderme adaxial e diminuíram o número de células epidérmicas em ambos os lados da folha. em relação ao controle, os retardantes de crescimento aumentaram em maior nível a espessura do parênquima lacunoso do que os promotores de crescimento.

The objective of this work was to evaluate the effect of plant growth regulators GA3 (50 mg. l-1), NAA (100 mg. l-1), CCC (1500 mg. l-1) and SADH (3000 mg. l-1)on the anatomy of tomato leafs of Lycopersicon esculentum Mill. cv. 'Ângela Gigante'.The growth promoters increased the number of stomata per square millimeter on adaxial epiderm and decreased the number of epidermic cells on both sides of the leaves. In relation to the control, growth retardants increased the thickness of the lacunary parenchyma, more than the growth promoters.
Growth regulators and tomato leaf anatomy (Lycopersicon esculentum Mill.) cv. 'Ângela Gigante'
Keywords: reguladores vegetais; anatomia; folha; tomate; plant growth regulators; anatomy; leaf; tomato